Analisis Minat Mahasiswa Akuntansi Syariah Untuk Berkarir Menjadi Akuntan Publik: (Studi Kasus Universitas Islam Negeri Sumatera Utara) - Akbar S, M. Rifky (Maisyatuna, 2024)
This research is entitled Analysis of Sharia Accounting Students' Interests in Careers as Public Accountants (Case Study of Accounting Students at the State Islamic University of North Sumatra). The formulation of the problem in this research is whether accounting knowledge, job market considerations, and professional training influence the interest of accounting students at the State Islamic University of North Sumatra to pursue a career as a public accountant. This research aims to determine how accounting knowledge, job market considerations, and professional training influence this type of descriptive research with a quantitative approach. This primary data collection method was carried out using a questionnaire method which was distributed to respondents. The population in this study was the Accounting Examination Students of the Faculty of Economics, State Islamic University of North Sumatra, class of 2019, totaling 50 respondents. The research carried out obtained the following results. This shows that the professional training variable partially has a significant influence on students' interest in becoming public accountants by accounting students at the State Islamic University of North Sumatra or in other words, hypothesis (H3) is accepted. This means that accounting knowledge, job market considerations, and professional training have a positive influence on accounting students' interest in pursuing a career as a public accountant.